2020
DOI: 10.1177/0022146520952767
|View full text |Cite
|
Sign up to set email alerts
|

They Drive Me Crazy: Difficult Social Ties and Subjective Well-Being

Abstract: Using egocentric network data from the University of California Social Networks Study (1,136 respondents; 11,536 alters), this study examines how difficult ties—an unexplored form of social negativity—are associated with well-being. Findings show that well-being is affected by the quality of the relationship rather than its presence in the network. Having a nondifficult partner is associated with lower loneliness compared to having no partner, but having no partner and having a difficult partner are related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 47 publications
(82 reference statements)
0
18
0
Order By: Relevance
“…Physical health may be indirectly related to social network variables, and in this study, only direct effects were tested quantitatively. Effects of social networks on the physical health of chronic conditions could be through the influence of mental health which have a buffering effect hypothesised in other theories of social networks influence on health (Offer, 2020; O’Malley et al, 2012; Pietromonaco, & Collins, 2017; Uchino & Rook, 2020; Valente, 2010). Positive social relationships may buffer stress and improve coping and self‐care which then contributes to physical health.…”
Section: Discussionmentioning
confidence: 93%
“…Physical health may be indirectly related to social network variables, and in this study, only direct effects were tested quantitatively. Effects of social networks on the physical health of chronic conditions could be through the influence of mental health which have a buffering effect hypothesised in other theories of social networks influence on health (Offer, 2020; O’Malley et al, 2012; Pietromonaco, & Collins, 2017; Uchino & Rook, 2020; Valente, 2010). Positive social relationships may buffer stress and improve coping and self‐care which then contributes to physical health.…”
Section: Discussionmentioning
confidence: 93%
“…Despite the potential benefits of being cosseted by supportive others, a person might also experience this highly integrated environment as emotionally taxing or invasive (Mueller and Abrutyn 2016), in turn accentuating the distress induced by bereavement. A growing literature also underscores that well-meaning family and friends can inadvertently cause a person stress by being demanding, offering poorly considered advice, or failing to grasp the severity of a stressor facing an individual (Offer 2020; Small 2017; Song et al 2021). Specific to bereavement, a series of studies by Lehman, Wortman, and colleagues (Lehman, Ellard, and Wortman 1986; Wortman and Lehman 1985) found that individuals contending with the loss of a loved one were distressed by significant others who provided unsolicited advice, pushed for an expedited mourning process, or claimed shared understanding despite an absence of comparable experience.…”
Section: Discussionmentioning
confidence: 99%
“…Increased (vs. consistently high) relationship strain involving spouses or partners rather than children, friends, or relatives is associated with increased mortality (Birditt and Antonucci 2008). In two community studies of two age cohorts, the number of difficult or demanding alters and having difficult partners and adult children is positively associated with psychological distress only among older adults (Child and Lawton 2020; Offer 2020). Relationship strain with relatives is positively related to psychological distress directly for whites but indirectly for blacks through personal control (Lincoln, Chatters, and Taylor 2003).…”
Section: Social Networkmentioning
confidence: 99%